Type of physical activity, muscle strength, and pubertal stage as determinants of bone mineral density and bone area in adolescent boys - Nordstrom, P.; Pettersson, U.; Lorentzon, R. (Journal of Bone and Mineral Research, 1998)
The present study was conducted to evaluate the influence of different types of weight-bearing physical activity, muscle strength, and puberty on bone mineral density (BMD, g/cm2) and bone area in adolescent boys. Three different groups were investigated. The first group consisted of 12 adolescent badminton players (age 17.0 +/- 0.8 years) training for 5.2 +/- 1.9 h/week. The second group consisted of 28 ice hockey players (age 16.9 +/- 0.3 years) training for 8.5 +/- 2.2 h/week. The third group consisted of 24 controls (age 16.8 +/- 0.3 years) training for 1.4 +/- 1.4h/week. The groups were matched for age, height, and pubertal stage. BMD, bone mineral content (BMC, g), and the bone area of the total body, lumbar spine, hip, femur and tibia diaphyses, distal femur, proximal tibia, and humerus were measured using dual-energy X-absorptiometry. When adjusting for the difference in body weight between the groups, the badminton players were found to have significantly higher BMD (p < 0.05) of the trochanter and distal femur compared with the ice hockey players despite a significantly lower weekly average training. The badminton players had higher BMD compared with the control with the control group at all weight-bearing BMD sites, except at the diaphyses of the femur and tibia and lumbar spine. The independent predictors of bone density were estimated by adjusting BMC for the bone area in a multivariate analysis among all subjects (n = 64). Accordingly, the bone density of all sites except the spine was significantly related to muscle strength and height, and the bone density of the total body, neck, trochanter, distal femur, and proximal tibia was significantly related to type of physical activity (beta = 0.09-0.33, p < 0.05). The bone area values at different sites were strongly related to muscle strength and height and less strongly related to the type of physical activity and pubertal stage. In conclusion, it seems that during late puberty in adolescent boys the type of weight-bearing physical activity is an important determinant of bone density, while the bone area is largely determined by parameters related to body size. The higher BMD at weight-bearing sites in badminton players compared with ice hockey players, despite significantly less average weekly training, indicates that physical activity including jumps in unusual directions has a great osteogenic potential.